Navigating complex financial decisions at retirement: evidence from annuity choices in public sector pensions. (29th January 2019) - Clark, Robert L.; Hammond, Robert G.; Vanderweide, David
Abstract: Choices regarding the disposition of wealth at retirement can have substantial implications for retirement income security. We analyze the factors determining annuity payout option choices within the context of a public sector defined pension plan with no default annuity option. Using combined administrative records and survey data, we explore the role of individual and household characteristics as well as risk preferences, time preferences, and financial literacy. We also document retiree well-being and satisfaction with retirement decision making. The evidence is consistent with predictions over which households might benefit most from each annuity option. Comparing retirees who chose different types of annuities, we find that these groups of retirees report very different levels of well-being in retirement. All retirees report lower levels of retirement income security over time, with strong differences among those who chose different types of annuities.